Solid surface fluorescence methodology for fast monitoring of 2,4-dichlorophenoxyacetic acid in seed samples - Alesso, Magdalena (2017)
A new method for pre-concentration/separation and determination of 2,4-dichlorophenoxyacetic acid (2,4-D) by solid-surface fluorescence (SSF) is proposed. The herbicide was complexed with Rhodamine B at pH 7.0 in the presence of phosphate buffer and anionic surfactant admicelles. A Nylon membrane was selected as a solid support for SSF measurement and the presence of 2,4-D was evident by the RhB quenching effect. Under optimal experimental conditions, the limit of detection and quantification were 6.93 and 21 ng L−1 , respectively, and the linear range was obtained from 0.021 to 22.11 μg L−1 2,4-D concentration. The developed methodology showed good sensitivity and adequate selectivity, and it was applied to the 2,4-D determination in seed samples. The SSF represents a simple and fast alternative to conventional methods of analysis, employing an existing instrument in most laboratories.